PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP PEMAHAMAN KONSEP STATISTIKA - imas yuly tresnanty (IKIP Siliwangi, 2019)
This study aims to determine the effect of problem based learning model to understanding of statistic concepts in the fifth grade of primary school. The method used was quasi experiment with nonrandomized pretest-posttest control group as a design study. Subjects of this study are 66 students in the fifth grade of primary school consisting of 33 students experimentation group and 33 control group students. The instrument used is a test understanding concepts The experimental group applying problem based learning model, while the control group applying convensional model. The results showed that there are significant differences of increase of student’s understanding concept between experimental and control group that are shown in t-test N-gain result at 0.00 with experiment’s N-gain average score at 0.8 and control’s at 0.6. So it can be concluded that problem based learning model to give effect to increase understanding of the concept of higher than convensional model. Keywords: problem based learning models, conventional models, and conceptual understanding